Population-Based Cohort Study of Anti-Infective Medication Use before and after the Onset of Type 1 Diabetes in Children and Adolescents - Fazeli Farsani, Soulmaz (American Society for Microbiology, 2014)
A population-based cohort study was conducted in the Dutch PHARMO database to investigate prevalence and patterns of anti-infective medication use in children and adolescents with type 1 diabetes (T1D) before and after the onset of this disease. All patients <19 years with at least 2 insulin prescriptions (1999 to 2009) were identified (T1D cohort) and compared with an age- and sex-matched (ratio: 1 up to 4) diabetes-free reference group. The prevalence and average number of anti-infective use was studied from (up to) 8 years before until a maximum of 4 years after the onset of T1D. A total of 925 patients with T1D and 3,591 children and adolescents in the reference cohort (51% boys, mean age of 10.1 [standard deviation, 4.5] years) were included. The overall prevalence of anti-infective use (62.6 compared to 52.6%, P < 0.001) and average number of prescriptions (2.71 compared to 1.42 per child, P < 0.001) in the T1D cohort were significantly higher than those in the reference cohort after the onset of diabetes. This pattern was consistent across sex and age categories and already observed in the year before the onset of type 1 diabetes. Patients in the T1D cohort received more antibacterials (49.8 compared to 40%, P < 0.001), antimycotics (4.0 compared to 1.3%, P < 0.001), antivirals (2.5 compared to 0.4%, P < 0.001), and second-line antibiotics, such as aminoglycosides, quinolones, and third-generation cephalosporins and carbapenems. Our findings that elevated anti-infective use in the T1D cohort exists in the period before the onset of type 1 diabetes and the consumption of more second-line anti-infective compounds in this time period warrant further research.